Hydrothermal liquefaction: A technological review on reactor design and operating parameters. (February 2023) - Elhassan, Mohamed; Abdullah, Rosnah; Kooh, Muhammad Raziq Rahimi; Chou Chau, Yuan-Fong
Abstract: Hydrothermal liquefication (HTL) is a thermochemical process that occurs in the presence of water. HTL converts lignocellulose biomass (2nd generation biomass) into useful products via the breakage and polymerization of biomass at the cellular level into solid, liquid, and negligible gas products. The quality, quantity, and physical product state depend on reactor design and process parameters. HTL has the highest reported bio-oil yield (80 wt%) among thermochemical processes due to parameters optimization and water catalytic behavior. HTL's wide range of applications sets it apart from other thermochemical processes. For instant, solid biochar and liquid products are used for water treatment, and fuel, respectively. However, products may need further treatment depending on the application. This review discusses thermochemical processes, feedstock categorization, HTL critical parameters, types of reactors, product applications, and limitations. Furthermore, this paper describes the mathematical and kinetic modeling steps to calculate process efficiency and reaction outcome. Graphical abstract: Unlabelled Image Highlights: The quantity and quality of biofuel yield rely on conversion process parameters. Feedstock characteristics and biofuel application influence reactor design. Kinetic modeling and software indicate potential process pathways. Hydrothermal process byproducts have a wide range of beneficial applications. Kinetic modeling, mitigation cost and TRL can predict process feasibility.